PENYISIHAN NITRAT, COD, DAN TSS AIR SUMUR TPA JABON DENGAN ELEKTROKOAGULASI DAN ANALISIS TIMBULAN LUMPUR - Naniek Ratni J.A.R; Anastasia Adellya Putri Witjaksono (EnviroUS, 2022)
Residential well water located close to the TPA location has been regulated in SNI 03-3241-1997, which must not be less than 100 m apart. But in reality the distance between the settlement and the landfill is only 600 m so that the well water in the settlement is polluted, therefore this study was conducted to set aside the nitrate, COD, and TSS parameters by electrocoagulation. This study aims to make people in the settlements get clean water solutions and also to know the characteristics of sludge generation in the electrocoagulation reactor. The result of the study showed that the highest nitrate removal rate was 86,88%, COD removal was 78,66%, and TSS removal was 99,70%. While the sludge content obtained COD of 507.6 mg/L, TSS of 9.06 mg/L, and aluminum of 0.3 mg/L. The results of the test on the sludge generation require further research on its processing.